Pengaruh Suasana Cafe, Fasilitas dan Varian Produk Terhadap Keputusan Pembelian Pada Cafe Segelas Kopi Kota Palopo - Syahdi, Muhammad Zadli; Asma, Tiara; Sari Parenta, Novita; Basri, Eka; Damayanti, Alfina (Movere Journal, 2025)
This study aims to analyze the influence of cafe atmosphere, facilities, and product variety on purchasing decisions at Cafe Segelas Kopi in Palopo City. The background of this research stems from the increasing competition in the culinary business, particularly cafes, which requires business owners to pay more attention to aspects such as ambiance, facility comfort, and product diversity to attract consumer interest. This research employed a quantitative approach with data collection techniques including questionnaires, observations, and interviews. The sample consisted of 30 respondents, determined using incidental sampling. Data analysis was carried out using multiple linear regression with SPSS software. The results showed that the cafe atmosphere, facilities, and product variety simultaneously had a significant effect on purchasing decisions. Furthermore, partially, the variables of café atmosphere and product variants had a positive influence on purchasing decisions, while the variable of facilities did not. This finding emphasizes the importance of managing a comfortable atmosphere, providing adequate facilities, and attractive product variants in increasing customer appeal and loyalty at Cafe Tengkorak Kopi, Palopo City.